Hard vinyl chloride-based copolymer and method for producing the same, vinyl chloride-based resin composition, and resin product

CN117801151BActive Publication Date: 2026-10-09BEIJING UNIV OF CHEM TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311794747.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2026-10-09
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

然而,结构单元(b)的亲水性比较强,因而在不希望亲水,甚至需要抗水的应用环境中,该共聚物的应用受限

Benefits of technology

[0046] This invention provides a rigid vinyl chloride copolymer that combines excellent biocompatibility, water resistance, transparency, self-plasticizing properties, processability, and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117801151B_ABST
    Figure CN117801151B_ABST
Patent Text Reader

Abstract

This invention relates to a rigid vinyl chloride copolymer and its preparation method, a vinyl chloride resin composition, and resin articles. The rigid vinyl chloride copolymer of this invention comprises a vinyl chloride-based structural unit (a), a structural unit (b) based on a monomer shown in formula (1), and optionally a structural unit (c) based on a monomer shown in formula (2), wherein in formula (1), R1 is selected from hydrogen and alkyl groups having 1 to 6 carbon atoms; R2 is selected from alkyl groups having 1 to 5 carbon atoms; each R3 is independently selected from hydrogen and alkyl groups having 1 to 22 carbon atoms, but not simultaneously hydrogen; in formula (2), R4 is selected from hydrogen and methyl; R5 is selected from alkyl groups having 1 to 18 carbon atoms, hydroxyalkyl groups having 1 to 18 carbon atoms, alkoxyalkyl groups having 1 to 18 carbon atoms, aminoalkyl groups having 1 to 18 carbon atoms, and cycloalkyl groups having 3 to 18 heteroatoms; the total content of structural units (b) and (c) is 1 to 20% by mass relative to 100% by mass of the total mass of the rigid vinyl chloride copolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of vinyl chloride resin synthesis, specifically to a rigid vinyl chloride copolymer and its preparation method, vinyl chloride resin compositions, and resin products. Background Technology

[0002] Polyvinyl chloride (PVC) resin is produced by free radical polymerization of vinyl chloride monomer (VC). It is one of the five major general-purpose resins in synthetic materials, ranking third in global production volume after polyethylene and polypropylene. Due to its excellent chemical resistance, chemical stability, thermoplasticity, and low manufacturing cost, PVC resin is widely used in construction, water supply, daily necessities, and biomedical fields.

[0003] Because PVC molecular chains are highly polar, their movement is restricted, increasing the processing difficulty of PVC resin. Therefore, plasticizers are added during PVC processing to reduce melt viscosity and improve PVC flexibility. Currently, phthalate esters (PAEs), represented by dioctyl phthalate (DEHP), are the main (approximately 70% or more) plasticizers used in PVC resin processing. However, PAEs are toxic small-molecule plasticizers. During the use of PVC resin products, plasticizer molecules easily migrate to the product surface, causing a decline in product performance. Especially in the field of medical products, small-molecule PAE plasticizers gradually migrate from the PVC resin product during use, entering the bloodstream or body fluids, or entering the human body through other contact routes, causing physiological harm. Currently, one of the research hotspots is the development of environmentally friendly, non-toxic / low-toxic plasticizers. Despite rapid progress in this area, the problem of plasticizer migration remains unsolved.

[0004] To address the migration problem of small-molecule plasticizers, an effective approach is considered to be to prepare vinyl chloride-based copolymers by copolymerizing vinyl chloride with plasticizing monomers, thereby endowing polyvinyl chloride resin with self-plasticizing properties. However, due to the characteristics of vinyl chloride monomers themselves, such as low monomer activity, high monomer chain transfer constant, high free radical activity, and a large difference in polymerization reactivity with other conventional monomers, vinyl chloride is difficult to copolymerize with other monomers through ordinary free radical polymerization. Therefore, currently, modified polyvinyl chloride resins are mainly prepared through PVC post-graft modification and living polymerization technology. Typically, the evaluation of the migration resistance of modified polyvinyl chloride resins considers whether the resulting resin contains components that are prone to migration due to the introduction of plasticizing components into the molecular chain, such as short molecular chains or molecular chains with excessively high plasticizing component content.

[0005] For example, Non-Patent Literature 1 utilizes the ring-opening reaction of caprolactone and propargyl alcohol to first synthesize polycaprolactone (PCL-Alkyne) with alkynyl end groups. Then, it undergoes a click reaction with azid-treated PVC resin (PVC-N3) under ultraviolet light, successfully covalently grafting PCL-Alkyne onto the PVC side chains. DSC testing shows that the introduction of PCL significantly lowers the glass transition temperature of the PVC resin, resulting in a good self-plasticizing effect. However, the raw materials used in Non-Patent Literature 1 are expensive, and the production method is relatively complex. Therefore, the main significance of this technology lies in scientific research, not in industrial application. Furthermore, azid-treated PVC essentially sacrifices the chlorine atoms that contribute significantly to the performance of PVC, which is detrimental to practical use.

[0006] For example, Non-Patent Literature 2 reports the modification of polyvinyl chloride (PVC) using living polymerization technology. Utilizing the unstable chlorine content on the PVC molecular chain as reaction sites, PVC resin is grafted with butyl acrylate and 2-ethylhexyl acrylate via the ATRP method to synthesize PVC-BA and PVC-EHA graft polymers. However, Non-Patent Literature 2 does not address the self-plasticizing properties. Furthermore, the resins obtained through this technology often contain residual transition metal compounds, resulting in poor durability in practical use.

[0007] For example, Non-Patent Literature 3 describes the modification of polyvinyl chloride resin through reactive blending. A PVC suspension containing monomers, initiators, and crosslinking agents is subjected to in-situ polymerization in a twin-screw extruder to obtain molten blends such as PVC / PMMA, PVC / PVAc, PVC / PBA, and PVC / PEHA. Since the reaction temperature in the extruder is 180°C, the resulting products are mostly low-molecular-weight polymers, effectively plasticizing PVC. However, this process route is prone to thermal decomposition of PVC and requires sophisticated equipment, making industrial production difficult.

[0008] For example, in Non-Patent Literature 4, butyl acrylate monomer and vinyl chloride are subjected to suspension polymerization to prepare a butyl acrylate-vinyl chloride copolymer. However, according to Non-Patent Literature 5, the amount of butyl acrylate used is only 10% or less. This is because when this value reaches 10%, the resulting resin is prone to agglomeration. In addition, since the content of butyl acrylate-based structural units that can be introduced into the resulting resin is low, the self-plasticizing properties are limited.

[0009] For example, Non-Patent Literature 5 describes the study of suspension copolymerization of VC and BA using a single-electron transfer-degenerate chain transfer living radical polymerization (SET-DTLRP) method. A homogeneous polyvinyl chloride-polybutyl acrylate random copolymer (PVC-PBA) was synthesized in one step. DMTA results showed that as the PBA content gradually increased from 10% to 40%, the Tg of the PVC-PBA vinyl chloride copolymer resin decreased from 70°C to 25°C. Although the living polymerization method is suitable for adjusting the structure of the resulting copolymer resin, this technology has high requirements for the production process, high costs, and drawbacks such as residual metal ions in the product and complex post-processing, thus lacking industrial application value.

[0010] However, when using ordinary free radical polymerization, the polymerization of vinyl chloride and acrylate copolymers, especially vinyl chloride and butyl acrylate and vinyl chloride and isooctyl acrylate, can significantly improve the toughness and elongation at break of the product. However, due to the difference in polymerization activity between acrylate monomers and vinyl chloride, homopolymers of acrylate are easily generated during the copolymerization process. The homopolymers of acrylate present in the system cause the product to be opaque due to compatibility issues with polyvinyl chloride.

[0011] Furthermore, traditionally known vinyl chloride-vinyl acetate copolymers (i.e., vinyl chloride / vinyl acetate copolymers) are generally considered to possess self-plasticizing properties. However, in practical applications, the self-plasticizing properties of vinyl chloride-vinyl acetate resins still need improvement. Additionally, vinyl chloride-vinyl acetate resins have low tensile strength, therefore they are mostly used in adhesives or as processing aids in the preparation of melt-molded products, and rarely as the main material for melt-molded products.

[0012] As mentioned above, most of the currently disclosed technologies are only in the scientific research stage and have little industrial practical value; while technologies suitable for industrial production often have difficulty achieving excellent self-plasticization and have poor control over the product structure.

[0013] Furthermore, from an industrial application perspective, it is desirable for vinyl chloride polymers with self-plasticizing properties to also have excellent processability. This is because, even if plasticization of vinyl chloride polymers is successful (achieved through the addition of plasticizers and / or the polymer possesses self-plasticizing properties), there are still situations where the plasticized melt is not easy to process, sometimes requiring the addition of other processing aids (e.g., ACR).

[0014] In addition, the inventors have previously proposed a rigid vinyl chloride copolymer that comprises, in a specific ratio, vinyl chloride-based structural units (a) and CH2=CR1COO(R2O)-based structural units. xThe copolymer contains structural unit (b) of the monomer shown in R3 and optional structural unit (c) based on the monomer shown in CH2=CR4COOR5 (refer to Patent Document 1). This copolymer can be obtained by a simple method and exhibits excellent self-plasticizing properties, transparency, and biocompatibility. However, structural unit (b) is relatively hydrophilic, thus limiting the application of this copolymer in environments where hydrophilicity is undesirable or even water resistance is required.

[0015] Therefore, there is a demand for vinyl chloride copolymers that combine self-plasticizing properties, processability, biocompatibility, transparency, and mechanical properties that meet those of traditional rigid resins, and can be used in water-resistant applications.

[0016] Existing technical documents

[0017] Non-patent literature

[0018] Non-patent literature 1: Eur. Polym. J., 2015, 66, 282–289.

[0019] Non-patent literature 2: J. Polym. Sci.: Part A: Polym. Chem., 2003, 41, 457–3462

[0020] Non-patent literature 3: Polym. Adv. Technol. 2005, 16, 495–504.

[0021] Non-patent literature 4: China Chlor-Alkali, 2013, 2, 17-22.

[0022] Non-patent literature 5: Eur. Polym. J., 2015, 73, 202–211.

[0023] Patent documents

[0024] Patent Document 1: CN 112574349 A Summary of the Invention

[0025] The problem the invention aims to solve

[0026] In view of the above-mentioned problems in the prior art, the object of the present invention is to provide a rigid vinyl chloride copolymer that has excellent biocompatibility, water resistance, transparency, self-plasticizing properties, processability and mechanical properties.

[0027] The present invention also aims to provide a method for preparing the above-mentioned vinyl chloride copolymer, a resin composition comprising the above-mentioned vinyl chloride copolymer, and articles made from the resin composition.

[0028] Solution for solving the problem

[0029] According to the inventor's dedicated research, the above-mentioned technical problems can be solved by implementing the following technical solution:

[0030] [1]. A rigid vinyl chloride copolymer comprising: a vinyl chloride-based structural unit (a), a structural unit (b) based on a monomer shown in formula (1), and optionally a structural unit (c) based on a monomer shown in formula (2).

[0031]

[0032] In formula (1), R1 is selected from hydrogen and alkyl groups having 1 to 6 carbon atoms; R2 is selected from alkyl groups having 1 to 5 carbon atoms; each R3 is independently selected from hydrogen and alkyl groups having 1 to 22 carbon atoms, but not simultaneously hydrogen.

[0033]

[0034] In formula (2), R4 is selected from hydrogen and methyl, and R5 is selected from alkyl with 1 to 18 carbon atoms, hydroxyalkyl with 1 to 18 carbon atoms, alkoxyalkyl with 1 to 18 carbon atoms, aminoalkyl with 1 to 18 carbon atoms, and cycloalkyl with 3 to 18 heteroatoms.

[0035] The total content of structural units (b) and (c) is 1 to 20% by mass relative to 100% of the total mass of the rigid vinyl chloride copolymer.

[0036] [2]. According to the rigid vinyl chloride copolymer described in [1], in formula (1), R1 is selected from hydrogen and methyl; R2 is selected from alkyl groups having 1 to 4 carbon atoms; each R3 is independently selected from hydrogen and alkyl groups having 1 to 18 carbon atoms, but not simultaneously from hydrogen.

[0037] [3]. The rigid vinyl chloride copolymer according to [1] or [2], wherein, in formula (2), R5 is selected from alkyl with 1 to 10 carbon atoms, hydroxyalkyl with 1 to 10 carbon atoms, alkoxyalkyl with 1 to 10 carbon atoms, aminoalkyl with 1 to 10 carbon atoms, and cycloalkyl with 3 to 10 heteroatoms.

[0038] [4]. The rigid vinyl chloride copolymer according to any one of [1] to [3], wherein the content of structural unit (b) is 0.5 to 19% by mass relative to 100% by mass of the total mass of the rigid vinyl chloride copolymer.

[0039] [5]. The rigid vinyl chloride copolymer according to any one of [1] to [4], wherein the content of structural unit (c) is 1 to 19.5% by mass relative to 100% by mass of the total mass of the rigid vinyl chloride copolymer.

[0040] [6]. The rigid vinyl chloride copolymer according to any one of [1] to [5], wherein the mass ratio of structural unit (b) to structural unit (c) in the rigid vinyl chloride copolymer is 1 / 20 to 10 / 1.

[0041] [7]. The rigid vinyl chloride copolymer according to any one of [1] to [6], wherein the elongation at break of the rigid vinyl chloride copolymer is less than 140%; and the number average molecular weight of the rigid vinyl chloride copolymer is 40,000 to 250,000.

[0042] [8]. A method for preparing a rigid vinyl chloride copolymer according to any one of [1] to [7], comprising: subjecting a raw material comprising vinyl chloride, a monomer of formula (1) and optionally a monomer of formula (2) to a copolymerization reaction.

[0043] [9]. A vinyl chloride resin composition comprising a rigid vinyl chloride copolymer according to any one of [1] to [7].

[0044]

[10] . A resin article made from a vinyl chloride resin composition according to [9].

[0045] The effects of the invention

[0046] This invention provides a rigid vinyl chloride copolymer that combines excellent biocompatibility, water resistance, transparency, self-plasticizing properties, processability, and mechanical properties.

[0047] By copolymerizing vinyl chloride with the monomers shown in formula (1) and optionally the monomers shown in formula (2) in a specific ratio, the resulting vinyl chloride copolymer has excellent mechanical properties that satisfy rigid vinyl chloride resins. At the same time, on the one hand, due to the introduction of plasticizing segments into the molecular chain of polyvinyl chloride, the resulting vinyl chloride copolymer can be well plasticized during processing even without the addition of plasticizers, i.e., it exhibits self-plasticizing properties. On the other hand, the resulting vinyl chloride copolymer can also exhibit excellent processability even without the addition of processing aids (in this invention, "excellent processability" refers to the property of easy handling of the melt during melt plasticizing / forming).

[0048] Surprisingly, the rigid vinyl chloride copolymer of the present invention also has excellent transparency.

[0049] Moreover, the rigid vinyl chloride copolymer of the present invention exhibits better water resistance because it does not contain hydrophilic ether chain groups (polyoxyalkylene groups) as shown in Patent Document 1.

[0050] Furthermore, the vinyl chloride copolymers of the present invention are not biotoxic. Moreover, since articles made from the vinyl chloride copolymers of the present invention may not contain plasticizers, they may also have good biological properties (such as non-cytotoxicity, good biocompatibility, and non-coagulation).

[0051] The present invention also provides a method for manufacturing the above-mentioned vinyl chloride copolymer, which realizes the copolymerization of vinyl chloride with each comonomer through a simple method that is conducive to industrial production.

[0052] The present invention further provides a vinyl chloride resin composition comprising the above-mentioned vinyl chloride copolymer and a resin article made from the resin composition. Detailed Implementation

[0053] Various exemplary embodiments, features, and aspects of the present invention will be described in detail below. The term "exemplary" as used herein means "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as superior to or better than other embodiments.

[0054] Furthermore, to better illustrate the present invention, numerous specific details are set forth in the following detailed embodiments. Those skilled in the art should understand that the present invention can be practiced without certain specific details. In other instances, methods, means, apparatus, and steps well known to those skilled in the art have not been described in detail in order to highlight the spirit of the present invention.

[0055] Unless otherwise stated, all units used in this specification are international standard units, and all numerical values ​​and ranges appearing in this invention should be understood to include systematic errors that are unavoidable in industrial production.

[0056] In this specification, the range of values ​​referred to as "value A to value B" refers to the range including the endpoint values ​​A and B.

[0057] In this specification, the numerical ranges referred to by "above" and "below" are ranges that include endpoint values.

[0058] In this specification, the numerical ranges indicated by "greater than" and "less than" refer to the ranges excluding endpoint values.

[0059] Unless otherwise specified, "%" in this instruction manual refers to weight percentage.

[0060] In this specification, the word "may" can mean both performing a certain treatment and not performing a certain treatment, or it can mean both having a certain component and not having a certain component.

[0061] In this specification, "optional" or "optionally" means that the event or situation described below may or may not occur, and the description includes both the scenario in which the event occurs and the scenario in which the event does not occur.

[0062] In this specification, "alkyl" or "alkylene" means a straight-chain, branched, or cyclic unsubstituted "alkyl" or "alkylene", and "aryl" or "arylene" means an aromatic ring (benzene ring, naphthalene ring, etc.) with no other substituents other than an alkyl group.

[0063] In this specification, a “structural unit” in a polymer refers to a polymeric unit derived from a monomer formed by monomer polymerization, and a polymeric unit formed by processing the polymer to transform a portion of that polymeric unit into other structures.

[0064] In this instruction manual, when "room temperature" or "room temperature" is used, the temperature can be between 10 and 40°C.

[0065] In this specification, the phrase “selected from A, B, ... and E” means that at least one of the groups consisting of the items (A, B, ..., E) is selected, covering any one of the items and any combination of two or more of the items.

[0066] In this specification, references to "some specific / preferred embodiments," "other specific / preferred embodiments," "implementation," etc., refer to specific elements (e.g., features, structures, properties, and / or characteristics) related to the described implementation that are included in at least one of the embodiments described herein, and may or may not be present in other embodiments. Furthermore, it should be understood that these elements may be combined in any suitable manner in various embodiments.

[0067] <vinyl chloride copolymer>

[0068] The rigid vinyl chloride copolymer of the present invention comprises: a vinyl chloride-based structural unit (a), a structural unit (b) based on a monomer shown in formula (1), and optionally a structural unit (c) based on a monomer shown in formula (2).

[0069]

[0070] In formula (1), R1 is selected from hydrogen and alkyl groups having 1 to 6 carbon atoms; R2 is selected from alkyl groups having 1 to 5 carbon atoms; each R3 is independently selected from hydrogen and alkyl groups having 1 to 22 carbon atoms, but not simultaneously hydrogen.

[0071]

[0072] In formula (2), R4 is selected from hydrogen and methyl, and R5 is selected from alkyl with 1 to 18 carbon atoms, hydroxyalkyl with 1 to 18 carbon atoms, alkoxyalkyl with 1 to 18 carbon atoms, aminoalkyl with 1 to 18 carbon atoms, and cycloalkyl with 3 to 18 heteroatoms.

[0073] The total content of structural units (b) and (c) is 1 to 20% by mass relative to 100% of the total mass of the rigid vinyl chloride copolymer.

[0074] The rigid vinyl chloride copolymer of the present invention comprises a vinyl chloride-based structural unit (a) and a monomer-based structural unit (b) of formula (1), but excludes a monomer-based structural unit (c) of formula (2), or comprises three structural units: a vinyl chloride-based structural unit (a), a monomer-based structural unit (b) of formula (1), and a monomer-based structural unit (c) of formula (2). In some preferred embodiments, from the viewpoint of better achieving the technical effects of the present invention, the rigid vinyl chloride copolymer of the present invention comprises three structural units: a vinyl chloride-based structural unit (a), a monomer-based structural unit (b) of formula (1), and a monomer-based structural unit (c) of formula (2).

[0075] The structural units of the vinyl chloride copolymer of the present invention are described in detail below.

[0076] (Structural Unit (a))

[0077] Structural unit (a) is a structural unit based on vinyl chloride.

[0078] (Structural Unit (b))

[0079] Structural unit (b) is a structural unit based on the single unit shown in equation (1).

[0080]

[0081] In the vinyl chloride copolymers of the present invention, structural unit (b) provides self-plasticizing properties, processability, water resistance, and transparency. The monomers shown in formula (1) above exhibit good copolymerization properties with vinyl chloride (and the monomers shown in formula (2) described later), and can copolymerize with vinyl chloride (and the monomers shown in formula (2) described later) in a wide range of proportions even in ordinary free radical polymerization systems. Furthermore, when the monomers shown in formula (2) described later also participate in polymerization, the copolymerization properties between vinyl chloride and the monomers shown in formula (2) described later can be significantly improved. Therefore, the vinyl chloride copolymers of the present invention can possess the desired properties.

[0082] In formula (1), R1 is selected from hydrogen and alkyl groups having 1 to 6 carbon atoms, preferably from hydrogen and straight-chain or branched alkyl groups having 1 to 6 carbon atoms, more preferably from hydrogen and / or methyl, and even more preferably from hydrogen.

[0083] In formula (1), R2 is selected from alkyl groups having 1 to 5 carbon atoms, and from the viewpoint of obtaining superior self-plasticizing and processability, it is more preferably selected from alkyl groups having 1 to 4 carbon atoms. In addition, the alkyl group as R2 is preferably linear or branched. From the viewpoint of obtaining even better self-plasticizing and processability, R2 is further preferably methyl, ethyl, or / and propyl.

[0084] In formula (1), each R3 is independently selected from hydrogen and an alkyl group having 1 to 22 carbon atoms, but not simultaneously hydrogen. From the viewpoint of obtaining better self-plasticizing and processability, each R3 is more preferably independently selected from hydrogen and an alkyl group having 1 to 20 carbon atoms, and even more preferably independently selected from hydrogen and an alkyl group having 1 to 18 carbon atoms. When each R3 is simultaneously an alkyl group, they can be the same or different. In addition, the alkyl group as R3 is preferably linear or branched.

[0085] In some preferred embodiments, from the viewpoint of better achieving the desired effects of the invention, the total number of carbon atoms in the two R3s is preferably 1 to 24, more preferably 2 to 20. Here, when one of the two R3s is hydrogen, the "total number of carbon atoms in the two R3s" is the number of carbon atoms in the other R3, which is an alkyl group; when each of the two R3s is an alkyl group with 1 to 22 carbon atoms, the "total number of carbon atoms in the two R3s" is the total number of carbon atoms in the two alkyl groups.

[0086] When one of the two R3s is hydrogen, specific examples of the monomers shown in formula (1) above include, but are not limited to: vinyl 2-methylpropionate, vinyl 2-methylbutyrate, vinyl 2-methylpentanoate, vinyl 2-methylhexanoate, vinyl 2-ethylbutyrate, vinyl 2-ethylpentanoate, vinyl 2-ethylhexanoate (V2EH), vinyl 2-ethylheptanoate, vinyl 2-propylpentanoate, etc. These monomers can be used alone or in combination of two or more.

[0087] When each of the two R3s is an alkyl group having 1 to 24 carbon atoms, specific examples of the monomers shown in formula (1) above include, but are not limited to, the monomers shown in formula (1-X) (where X is 1 to 9). (Since commercially available products of this monomer are sometimes mixtures of isomers and only the total number of carbon atoms of the two R3s is indicated, the structures of some of the monomers shown in formulas (1-1) to (1-8) below are represented only by the total number of carbon atoms of the two R3s, without specifically listing the structures of each of the two R3s):

[0088]

[0089] In formula (1-1), the total number of carbon atoms in the two R3s is 2, and both R3s are methyl; in formula (1-2), the total number of carbon atoms in the two R3s is 3, one R3 is methyl, and the other R3 is ethyl; in formula (1-3), the total number of carbon atoms in the two R3s is 7; in formula (1-4), the total number of carbon atoms in the two R3s is 9; in formula (1-5), the total number of carbon atoms in the two R3s is 10; in formula (1-6), the total number of carbon atoms in the two R3s is 11; in formula (1-7), the total number of carbon atoms in the two R3s is 13; in formula (1-8), the total number of carbon atoms in the two R3s is 20; and in formula (1-9), the total number of carbon atoms in the two R3s is 22. These monomers can be used alone or in combination of two or more.

[0090] It should be noted that, for ease of description, in the specification of this invention and the following embodiments, in the exemplary monomers listed as monomers represented by formula (1) above, if the carbon number of each alkyl group adjacent to the carbonyl group is different, the alkyl group with the most carbons is designated as one R3, and the alkyl group with the fewest carbons is designated as R2. For example, in 2-ethylhexanoate, one R3 is butyl, one R3 is H, and R2 is ethyl; while in 2,2-dimethylhexanoate, one R3 is butyl, another R3 is methyl, and R2 is methyl.

[0091] (Structural Unit (c))

[0092] Structural unit (c) is a structural unit based on the single unit shown in equation (2).

[0093]

[0094] In the vinyl chloride copolymer of the present invention, structural unit (c) can also provide plasticizing effect, further improving the mechanical properties and water resistance of the vinyl chloride copolymer and reducing cost.

[0095] In formula (2), R4 is selected from hydrogen and methyl.

[0096] In formula (2), R5 is selected from alkyl groups having 1 to 18 carbon atoms, hydroxyalkyl groups having 1 to 18 carbon atoms, alkoxyalkyl groups having 1 to 18 carbon atoms, aminoalkyl groups having 1 to 18 carbon atoms, and cycloalkyl groups having 3 to 18 heteroatoms such as oxygen, nitrogen, and sulfur. In some preferred embodiments, from the viewpoint of better achieving the technical effects of the present invention, R5 is selected from alkyl groups having 1 to 10 carbon atoms, hydroxyalkyl groups having 1 to 10 carbon atoms, alkoxyalkyl groups having 1 to 10 carbon atoms, aminoalkyl groups having 1 to 10 carbon atoms, and cycloalkyl groups having 3 to 10 heteroatoms.

[0097] Furthermore, the alkyl, hydroxyalkyl, alkoxyalkyl, or aminoalkyl group as R3 is preferably linear or branched.

[0098] Note that "hydroxyalkyl" refers to an alkyl group in which any hydrogen atom is replaced by a hydroxyl group; "alkoxyalkyl" refers to an alkyl group in which any hydrogen atom is replaced by an alkoxy group; and "aminoalkyl" refers to an alkyl group in which any hydrogen atom is replaced by an amino group.

[0099] Specific examples of the monomers shown in formula (2) above include, but are not limited to, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, tert-pentyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate, isooctyl methacrylate, n-nonyl methacrylate, isononyl methacrylate, n-decyl methacrylate, isodecyl methacrylate, n-dodecyl methacrylate, undecyl methacrylate, and isobutyl methacrylate. Undecyl ester, cyclohexyl methacrylate, tert-butylcyclohexyl methacrylate, cyclooctyl methacrylate, glycidyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 2-hydroxyhexyl methacrylate, 6-hydroxyhexyl methacrylate, 8-hydroxyoctyl methacrylate, 10-hydroxydecyl methacrylate, methoxyethyl methacrylate, ethoxyethyl methacrylate, methoxypropyl methacrylate, ethoxypropyl methacrylate, dimethylaminomethyl methacrylate, dimethylaminoethyl methacrylate, dimethylaminopropyl methacrylate, isobornyl methacrylate, etc. These monomers can be used alone or in combination of two or more.

[0100] From the viewpoint of copolymerization with each monomer and adjustment of the self-plasticizing properties, applicability and mechanical properties of the resulting copolymer, it is preferred to select at least one selected from methyl methacrylate, glycidyl methacrylate, isobornyl methacrylate, ethyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl methacrylate, isooctyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, dimethylaminoethyl methacrylate, and hexyl methacrylate.

[0101] (Content of structural units (a), (b) and (c))

[0102] As long as the total content of structural unit (b) and structural unit (c) in the vinyl chloride copolymer of the present invention is 1 to 20% by mass, there are no particular restrictions on the content of each of the structural unit (a), structural unit (b) and optional structural unit (c), which can be appropriately selected according to the use of the vinyl chloride copolymer.

[0103] From the viewpoint of better improving the self-plasticizing properties, transparency, and mechanical properties of the vinyl chloride copolymer and better adapting the vinyl chloride copolymer of the present invention to the application field of rigid PVC, the total content of structural unit (b) and structural unit (c) in the vinyl chloride copolymer is preferably 1.2 to 19% by mass, more preferably 2 to 17.9% by mass.

[0104] In some preferred embodiments of the present invention, the content of structural unit (a) relative to 100% of the total mass of the vinyl chloride copolymer is preferably 80-99% by mass, more preferably 83-98.8% by mass, and even more preferably 85-98% by mass. When the content of structural unit (a) is greater than the above preferred range, the self-plasticizing and processability of the obtained vinyl chloride copolymer tends to deteriorate. When the content of structural unit (a) is less than the above range, the mechanical properties of the obtained vinyl chloride copolymer tend to fail to meet the mechanical property requirements of rigid vinyl chloride resin.

[0105] In some preferred embodiments of the present invention, the content of structural unit (b) relative to 100% of the total mass of the vinyl chloride copolymer is preferably 0.5 to 19% by mass, more preferably 1 to 18% by mass, and even more preferably 1.5 to 16% by mass. When the content of structural unit (b) is greater than the above preferred range, although it has a significant plasticizing effect on the vinyl chloride copolymer and improves its processability, the mechanical properties of the resulting vinyl chloride copolymer tend to decrease; when the content of structural unit (b) is less than the above range, the self-plasticizing properties, processability, transparency, and water resistance of the resulting vinyl chloride copolymer tend to deteriorate.

[0106] In a preferred embodiment of the rigid vinyl chloride copolymer of the present invention, which includes structural unit (c), from the viewpoint of better balancing self-plasticizing properties, mechanical properties, water resistance and reducing costs, the content of structural unit (c) is preferably 1 to 19.5% by mass, more preferably 2 to 18% by mass, and even more preferably 3 to 17% by mass, relative to 100% by mass of the total mass of the vinyl chloride copolymer.

[0107] In other preferred embodiments, the contents of each of the structural unit (a), structural unit (b), and structural unit (c) simultaneously satisfy the above-mentioned ranges relative to 100% of the total mass of the vinyl chloride copolymer.

[0108] In other preferred embodiments, from the viewpoint of more balanced consideration of water resistance, transparency, self-plasticizing properties, processability and mechanical properties, the mass ratio of structural unit (b) to structural unit (c) in rigid vinyl chloride copolymers is preferably 1 / 20 to 10 / 1, more preferably 1 / 15 to 2 / 1, and even more preferably 1 / 10 to 1 / 2.

[0109] (Structural units based on other monomers)

[0110] Without impairing the technical effects of the present invention, in addition to the structural unit (a) based on vinyl chloride, the structural unit (b) based on the monomer shown in formula (1), and the optional structural unit (c) based on the monomer shown in formula (2), the rigid vinyl chloride copolymer of the present invention may also include structural units based on other monomers.

[0111] There are no particular restrictions on other monomers, as long as they can copolymerize with any one of vinyl chloride, the monomer shown in formula (1), and the optional monomer shown in formula (2).

[0112] In this invention, preferably, examples of structural units based on other monomers include, but are not limited to, structural units based on vinyl ether monomers, structural units based on fluorinated (meth)acrylate monomers, structural units based on maleimide monomers, structural units based on acrylonitrile monomers, and structural units based on carboxyl-containing monomers. These structural units may exist alone or in combination in the vinyl chloride copolymers of this invention, thereby imparting desired properties to the vinyl chloride copolymers as needed.

[0113] In this invention, it is preferred that the rigid vinyl chloride copolymer of this invention does not include structural units based on polyalkylene glycol alkyl ether (meth) acrylate monomers, such as structural unit (b) contained in the vinyl chloride copolymer described in Patent Document 1.

[0114] Structural units based on vinyl ether monomers

[0115] The structural unit based on vinyl ether monomers is the structural unit based on the monomer shown in equation (3).

[0116] CH2=CHOR6 (3)

[0117] In formula (3), R6 is selected from straight-chain or branched alkyl groups having 1 to 10 carbon atoms, straight-chain or branched cycloalkyl groups having 3 to 10 carbon atoms, and straight-chain or branched hydroxyalkyl groups having 1 to 10 carbon atoms, which may be substituted with halogen atoms such as chlorine, bromine, and fluorine. Preferably, R6 is selected from straight-chain or branched alkyl groups having 1 to 8 carbon atoms, straight-chain or branched cycloalkyl groups having 3 to 8 carbon atoms, and straight-chain or branched hydroxyalkyl groups having 1 to 8 carbon atoms, which may be substituted with halogen atoms such as chlorine, bromine, and fluorine. In addition, the hydrogen atom in formula (3) (meaning the hydrogen atom in "CH2=CH-" in formula (3)) may also be substituted with halogen atoms such as chlorine, bromine, and fluorine.

[0118] Examples of monomers shown in formula (3) above include, but are not limited to, vinyl methyl ether, vinyl ethyl ether, vinyl n-propyl ether, vinyl isopropyl ether, vinyl tert-butyl ether, vinyl n-butyl ether, vinyl isobutyl ether, vinyl n-pentyl ether, vinyl cyclopentyl ether, vinyl cyclohexyl ether, 5-hydroxypentyl vinyl ether, 4-hydroxypentyl vinyl ether, 3-hydroxypentyl vinyl ether, 2-hydroxypentyl vinyl ether, 4-hydroxybutyl vinyl ether, 3-hydroxybutyl vinyl ether, 2-hydroxybutyl vinyl ether, 3-hydroxypropyl vinyl ether, and 2-hydroxypropyl vinyl ether. Vinyl n-butyl ether, vinyl isobutyl ether, 3-hydroxypropyl vinyl ether, and 4-hydroxybutyl vinyl ether are preferred. These monomers can be used alone or in combination of two or more.

[0119] When the rigid vinyl chloride copolymer of the present invention has a structural unit based on the monomer of the above formula (3), it can provide better self-plasticizing properties and also provides better biocompatibility and lubricity.

[0120] Structural units based on fluorinated (meth) acrylate monomers

[0121] The structural unit based on the fluorinated (meth)acrylate monomer is the structural unit based on the monomer shown in formula (4).

[0122] CH2=CR4COOR7 (4)

[0123] In formula (4), R4 is defined as above, and R7 is selected from linear or branched fluoroalkyl groups with 1 to 18 carbon atoms, fluorocycloalkyl groups with 3 to 18 carbon atoms, and fluorophenyl groups, preferably linear or branched fluoroalkyl groups with 1 to 12 carbon atoms, fluorocycloalkyl groups with 3 to 12 carbon atoms, and fluorophenyl groups. In addition, the hydrogen atom in formula (4) (meaning the hydrogen atom in "CH2=" in formula (4)) can also be replaced by halogen atoms such as chlorine, bromine, and fluorine.

[0124] Examples of monomers shown in formula (4) above include, but are not limited to, trifluoroethyl methacrylate, tetrafluoropropyl methacrylate, pentafluoropropyl methacrylate, pentafluorophenyl methacrylate, hexafluorobutyl methacrylate, heptafluorobutyl methacrylate, octafluoropentyl methacrylate, nonafluorohexyl methacrylate, dodecafluoroheptyl methacrylate, and tridecafluorooctyl methacrylate. Among these, trifluoroethyl methacrylate, pentafluorophenyl methacrylate, and hexafluorobutyl methacrylate are preferred. These monomers can be used alone or in combination of two or more.

[0125] When the rigid vinyl chloride copolymer of the present invention has a structural unit based on the monomer of the above formula (4), it can provide excellent processing lubricity (e.g., reduced adhesion to twin rollers or screws, reduced melt viscosity, etc.) and antibacterial / antifouling properties of the product.

[0126] Structural units based on maleimide monomers

[0127] Examples of maleimide monomers that form structural units based on maleimide monomers include, but are not limited to, N-methylmaleimide, N-ethylmaleimide, N-n-propylmaleimide, N-isopropylmaleimide, N-cyclohexylmaleimide, N-laurylmaleimide, and N-phenylmaleimide. These monomers can be used alone or in combination of two or more.

[0128] Structural units based on acrylonitrile monomers

[0129] Examples of acrylonitrile monomers that form structural units based on acrylonitrile monomers include, but are not limited to, acrylonitrile, methacrylonitrile, ethyl acrylonitrile, etc. These monomers can be used alone or in combination of two or more.

[0130] Structural units based on carboxyl-containing monomers

[0131] Examples of carboxyl-containing monomers that form structural units based on carboxyl-containing monomers include, but are not limited to, acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypropyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. These monomers can be used alone or in combination of two or more.

[0132] (glass transition temperature (Tg))

[0133] The glass transition temperature of the vinyl chloride copolymer of the present invention can reflect the structure of the copolymer, and is used in the present invention to represent the self-plasticizing property of the copolymer.

[0134] From the viewpoint of achieving both superior self-plasticizing and processability, the vinyl chloride-based copolymers of the present invention preferably have only one glass transition temperature. Furthermore, there is generally no particular limitation on this glass transition temperature, as long as it is lower than that of homopolymer polyvinyl chloride. However, the glass transition temperature is preferably lower than 120°C, more preferably lower than 100°C. When the glass transition temperature is greater than or equal to the above-mentioned upper limit, the self-plasticizing and processability of the vinyl chloride-based copolymers of the present invention tend to deteriorate. From the viewpoint of further ensuring the performance of rigid vinyl chloride-based copolymers, the glass transition temperature is preferably 50°C or higher, more preferably 60°C or higher.

[0135] In this invention, the glass transition temperature can be determined using a dynamic thermomechanical analyzer (DMTA).

[0136] (Number average molecular weight)

[0137] There is no particular limitation on the number-average molecular weight of the vinyl chloride copolymers of the present invention, and it can be appropriately selected according to the application. From the viewpoint of simultaneously achieving better mechanical properties and lower costs, the number-average molecular weight of the vinyl chloride copolymers of the present invention is preferably 40,000 to 250,000, more preferably 50,000 to 220,000, and even more preferably 60,000 to 200,000. When the number-average molecular weight is less than the above range, the mechanical properties of the copolymer resin, such as tensile strength and elongation at break, tend to decrease. When the number-average molecular weight is greater than the above range, the polymerization temperature tends to be too low, resulting in low conversion rate and increased production cost.

[0138] In this invention, the number-average molecular weight can be determined using gel permeation chromatography (GPC) with polystyrene as the standard.

[0139] (physical properties)

[0140] According to common understanding in the art, polyvinyl chloride (PVC) is usually processed with the addition of plasticizers. Therefore, PVC resins are classified into rigid PVC (e.g., plasticizer content less than 20%) and flexible PVC (e.g., plasticizer content more than 20%) based on the content of the added plasticizer, and these differences manifest in their mechanical properties and other physical properties. However, since the vinyl chloride copolymer of the present invention is a new copolymer distinct from PVC, and can be excellently plasticized even without the addition of plasticizers, the present invention mainly judges whether the PVC copolymer meets the requirements for rigid PVC in the art based on the range of tensile elongation at break. Specifically, in the present invention, the tensile elongation at break of the vinyl chloride copolymer, according to the test method of GB / T 1040-2006, is preferably less than 140%, more preferably 10-140%, even more preferably 11-138%, and still more preferably 12-135%.

[0141] In this invention, the tensile strength of the vinyl chloride copolymer is preferably 30 MPa or more, more preferably 35 MPa or more, according to the test method of GB / T 1040-2006.

[0142] In this invention, the hardness of the vinyl chloride copolymer according to the test method (Shore D) of GB / T 2411-2008 is preferably greater than 40, more preferably greater than 45.

[0143] In this invention, the light transmittance of the vinyl chloride copolymer is preferably greater than 75%, more preferably greater than 78%. Typically, the light transmittance is measured using a UV-Vis spectrophotometer by methods known in the art.

[0144] Particularly preferred is that the rigid vinyl chloride copolymer of the present invention simultaneously satisfies all of the above-mentioned physical property parameters.

[0145] <Preparation method of hard vinyl chloride copolymer>

[0146] The method for preparing the rigid vinyl chloride copolymer of the present invention is the same as the method for preparing the rigid vinyl chloride copolymer described above, which includes: subjecting a raw material comprising vinyl chloride, a monomer shown in formula (1) above and optionally a monomer shown in formula (2) above to a copolymerization reaction.

[0147] Details of vinyl chloride, the monomer shown in formula (1), the monomer shown in formula (2), and other monomers have been described above and will not be repeated here.

[0148] Examples of copolymerization reactions of the present invention include, but are not limited to, block polymerization, random polymerization, graft polymerization, and gradient polymerization. Among these, random polymerization is preferred from the viewpoint of more advantageously demonstrating the technical effects of the present application; that is, the molecular chains of the rigid vinyl chloride copolymers of the present invention preferably have a random structure. More preferably, the rigid vinyl chloride copolymers of the present invention are random copolymers.

[0149] As long as the rigid vinyl chloride copolymer of the present invention can be obtained, there are no particular limitations on the mechanism of the preparation method, and conventional free radical polymerization, living free radical polymerization, etc., can be used. However, from the viewpoint of being beneficial to industrial production, the preparation method of the rigid vinyl chloride copolymer of the present invention is based on the conventional free radical polymerization mechanism.

[0150] As a polymerization method, any polymerization method based on the free radical polymerization mechanism can be used, such as emulsion polymerization, solution polymerization, suspension polymerization, bulk polymerization, slurry polymerization, gas-phase polymerization, and interfacial polymerization. From the viewpoints of adjusting molecular weight and copolymer composition, and productivity, suspension polymerization, bulk polymerization, and emulsion polymerization are preferred.

[0151] (Ontology Aggregation Method)

[0152] The bulk polymerization method of the present invention is a well-known bulk polymerization method in the art. Specifically, the bulk polymerization method of the present invention is a polymerization method in which the polymerization system does not contain a dispersion medium. Preferably, the bulk polymerization method is carried out by polymerizing the monomers used in the present invention in the presence of an initiator.

[0153] When using the bulk polymerization method, there are no restrictions on the order or method of adding the monomers. The monomers can be added together or in batches in any combination.

[0154] Specific examples of initiators suitable for bulk polymerization include, but are not limited to: azo initiators, such as azobisisobutyronitrile, azobisisovalerate, and azobisisoheptanenitrile; organic peroxide initiators, such as tert-butyl peroxynivalenate, tert-butyl peroxynivalenate, disec-butyl peroxydicarbonate, bis(hexadecyl)dicarbonate peroxide, tert-pentyl peroxynivalenate, tert-butyl peroxynivalenate, di-(4-tert-butylcyclohexyl peroxydicarbonate), dicyclohexyl peroxydicarbonate, and dicarbonyl peroxydicarbonate. Examples of free radical initiators include diisopropyl peroxide, dibutyl peroxide dicarbonate, di(2-ethylhexyl) peroxide dicarbonate, tert-butyl peroxide 2-ethylhexanoate, ditetradecyl peroxide dicarbonate, tert-butyl peroxide acetate, cumyl peroxide neodecanoate, ditert-butyl peroxide, cyclohexylsulfonyl peroxide, benzoyl peroxide, diisobutyryl peroxide, 1,1,3,3-tetramethylbutyl peroxide neodecanoate, di-3-methoxybutyl peroxide dicarbonate, and 1,1,3,3-tetramethylbutyl peroxide pentanoate. These free radical initiators can be used alone or in combination of two or more. In particular, free radical initiators with a decomposition temperature of less than 80°C are preferred.

[0155] The amount of initiator relative to the total mass of the monomer is preferably 0.001 to 4% by mass, more preferably 0.01 to 2% by mass.

[0156] In addition, in the copolymerization of the present invention, a molecular weight regulator may be added according to the required molecular weight range. Specific examples of suitable molecular weight regulators include, but are not limited to, n-dodecyl mercaptan, tert-dodecyl mercaptan, mercaptoethanol, mercaptoacetic acid, trichloropropene, etc., with mercaptoethanol and n-dodecyl mercaptan being preferred.

[0157] The polymerization conditions can be appropriately selected based on the monomer composition and the decomposition temperature of the initiator. The polymerization temperature is preferably 0–100°C, more preferably 10–90°C, and most preferably 30–80°C. The polymerization time is preferably 1–72 hours, more preferably 1–24 hours, and most preferably 1–12 hours.

[0158] (Suspension polymerization method)

[0159] The suspension polymerization method of the present invention is a suspension polymerization method known in the art. Preferably, the suspension polymerization method of the present invention is carried out while the polymerization system is stirred.

[0160] The dispersion medium in suspension polymerization can be water or a mixture of water and a water-soluble organic solvent. Examples of such water-soluble organic solvents include, but are not limited to: alcohols such as methanol, ethanol, propanol, butanol, cyclohexanol, ethylene glycol, propylene glycol, glycerol, etc.; ketones such as acetone, butanone, cyclohexanone, etc.; polyol alkyl ethers such as ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, tetraethylene glycol monomethyl ether, and propylene glycol monoethyl ether; polyol aryl ethers such as ethylene glycol monophenyl ether and ethylene glycol monobenzyl ether; and nitrogen-containing heterocycles. Compounds such as N-methyl-2-pyrrolidone, N-hydroxyethyl-2-pyrrolidone, 2-pyrrolidone, 1,3-dimethylimidazolium ketone, and ε-caprolactam; amides such as formamide, N-methylformamide, formamide, and N,N-dimethylformamide; amines such as monoethanolamine, diethanolamine, triethanolamine, monoethylamine, diethylamine, and triethylamine; sulfur-containing compounds such as dimethyl sulfoxide, sulfolane, and thiodiethanol; propylene carbonate and ethylene carbonate.

[0161] From the viewpoint of easy recycling, water is the preferred dispersion medium. Various forms of water can be used, such as tap water, deionized water, and distilled water.

[0162] The dispersant used in suspension polymerization can be any dispersant known in the art, such as anionic dispersants, cationic dispersants, nonionic dispersants, or polymeric dispersants.

[0163] Specific examples of dispersants may include, but are not limited to: water-soluble organic polymers, such as partially hydrolyzed polyvinyl alcohol, salts of polyvinylpyrrolidone, polyacrylic acid, or polymethacrylic acid, synthetic polymers such as maleic anhydride / styrene copolymers, cellulose derivatives such as methylcellulose, hydroxymethylcellulose, hydroxypropylcellulose, and hydroxypropylmethylcellulose, natural polymers such as gelatin, protein, starch, and sodium alginate; and water-insoluble inorganic powders, such as magnesium carbonate, calcium carbonate, barium sulfate, calcium sulfate, calcium phosphate, talc, and kaolin; etc. These dispersants may be used alone or in combination of two or more. Considering the particle size and shape of the product, the transparency of the resin, and the film-forming properties, water-soluble organic polymers are preferred, and mixtures of polyvinyl alcohol and cellulose derivatives are more preferred. The amount of dispersant relative to 100 parts by weight of the dispersion medium is preferably 0.01 to 5% by weight, more preferably 0.05 to 3% by weight.

[0164] The monomer concentration in the system is preferably 10 to 60% by mass relative to the total mass of the dispersion medium, and more preferably 15 to 50% by mass.

[0165] When using suspension polymerization, there are no restrictions on the order or method of adding monomers. Monomers can be added together or in batches in any combination.

[0166] The ranges of molecular weight regulators, initiators, initiator dosages, and polymerization conditions (polymerization temperature and polymerization time, etc.) applicable to suspension polymerization are the same as those in "(bulk polymerization)" above, and will not be repeated here.

[0167] (Emulsion polymerization)

[0168] The emulsion polymerization method of the present invention is a well-known emulsion polymerization method in the art. Preferably, the emulsion polymerization method of the present invention is carried out while the polymerization system is stirred.

[0169] The type of dispersion medium is the same as that described in "(Suspension Polymerization)" above, and will not be repeated here.

[0170] The monomer concentration in the system is preferably 5 to 60% by mass relative to the total mass of the dispersion medium, and more preferably 10 to 40% by mass.

[0171] The emulsifier used in emulsion polymerization can be any emulsifier known in the art. Specific examples of the emulsifiers of the present invention may include, but are not limited to: nonionic emulsifiers, such as polyoxyethylene alkylphenyl ethers, polyoxyethylene alkyl ethers, polyoxyethylene styrene phenyl ethers, polyoxyethylene benzyl phenyl ethers, polyoxyethylene isopropylphenyl phenyl ethers, fatty acid polyethylene glycol ethers, polyoxyethylene dehydrated sorbitol fatty acid esters, dehydrated sorbitol fatty acid esters, etc.; anionic emulsifiers, such as fatty acid soaps, rosin acid soaps, alkyl sulfonates, alkyl aryl sulfonates, alkyl sulfates, alkyl sulfosuccinates, and sulfates, phosphates, ether carboxylates, sulfosuccinates, etc., of nonionic emulsifiers having polyoxyethylene chains; cationic emulsifiers, such as stearyltrimethylammonium salt, cetyltrimethylammonium salt, lauryltrimethylammonium salt, dialkyldimethylammonium salt, alkyldimethylbenzylammonium salt, alkyldimethylhydroxyethylammonium salt, etc.

[0172] The amount of emulsifier used is preferably 0.5 to 15% by mass, more preferably 1.0 to 10% by mass, relative to 100 parts by mass of the dispersion medium.

[0173] In addition, emulsifiers may not be used in the emulsion polymerization method of the present invention, that is, the emulsion polymerization method of the present invention may also be based on self-emulsion polymerization.

[0174] When using emulsion polymerization, there are no restrictions on the order or method of adding monomers. Monomers can be added together or in batches in any combination.

[0175] Specific examples of initiators suitable for emulsion polymerization include, but are not limited to: the initiators described in "(bulk polymerization)" above; redox initiators; and persulfates, such as ammonium persulfate, potassium persulfate, etc. These initiators can be used alone or in combination.

[0176] The amount of initiator relative to the total mass of the monomer is preferably 0.001 to 4% by mass, more preferably 0.01 to 2% by mass.

[0177] In addition, the types of molecular weight regulators applicable to emulsion polymerization are the same as those in "(bulk polymerization)" above, and will not be repeated here.

[0178] The polymerization conditions can be appropriately selected based on the monomer composition and the decomposition temperature of the initiator. The polymerization temperature is preferably 10–90°C, and most preferably 30–80°C. The polymerization time is preferably 1–72 hours, more preferably 1–24 hours, and most preferably 1–12 hours.

[0179] <Venerine Chloride Resin Compositions>

[0180] The vinyl chloride-based resin composition of the present invention includes the above-mentioned rigid vinyl chloride copolymer.

[0181] In addition to the rigid vinyl chloride copolymer of the present invention, the vinyl chloride resin composition of the present invention may optionally include other components, examples of which include other resins, such as other vinyl chloride resins, propylene resins, ethylene resins, polyester resins such as polyethylene terephthalate, styrene resins, fluororesins, silicone resins, polyamide resins, polyimide resins, etc.; rubbers, such as styrene-butadiene rubber, nitrile rubber, butyl rubber, chloroprene rubber, isoprene rubber, cis-butadiene rubber, ethylene propylene rubber, ethylene propylene diene rubber, silicone rubber; thermoplastic elastomers, such as olefin-based thermoplastic elastomers, styrene-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, polyester-based thermoplastic elastomers, polyvinyl chloride-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, fluoropolymer-based thermoplastic elastomers, etc. These can be used alone or in combination of two or more. Relative to 100 parts by weight of the vinyl chloride-based resin composition, the content of the other components is preferably 50 parts by weight or less, more preferably 30 parts by weight or less, even more preferably 10 parts by weight or less, and even more preferably 0 parts by weight.

[0182] The vinyl chloride-based resin compositions of the present invention may optionally include, in any amount, a variety of additives commonly known in the art, such as fillers, pigments, plasticizers, ultraviolet absorbers, light stabilizers, matting agents, surfactants, leveling agents, surface conditioners, degassing agents, heat stabilizers, antistatic agents, rust inhibitors, silane coupling agents, antifouling agents, antibacterial agents, foaming agents, crosslinking agents, lubricants, processing aids (e.g., ACR, etc.). These can be used alone or in combination of two or more.

[0183] In some preferred embodiments, the vinyl chloride-based copolymers of the present invention do not contain plasticizers because of their excellent self-plasticizing properties. In other preferred embodiments, the vinyl chloride-based resin compositions of the present invention do not contain processing aids to improve processability because of their excellent processability.

[0184] The vinyl chloride-based resin compositions of the present invention can be prepared by methods commonly known in the art. For example, all components constituting the vinyl chloride-based resin compositions of the present invention can be mixed using standard mixing equipment such as Banbury or Brabender mixers, extruders, kneaders, and two-roll mills. There are no particular limitations on the method of composition preparation, and the above mixing can be carried out in a single-stage or multi-stage manner depending on the desired composition. There are also no particular limitations on the mixing temperature and mixing speed, which can be appropriately selected according to the desired composition.

[0185] <Resin Products>

[0186] The resin article of the present invention is a rigid PVC molded article made from the above-described vinyl chloride-based resin composition. In some specific embodiments, the resin article of the present invention is preferably a melt-molded article, for example, an article obtained by extrusion molding, injection molding, blow molding, die (pressure) molding, calendering, etc.

[0187] The resin products of the present invention can be used for various purposes known in the art, such as PVC sheets, PVC pipes, PVC profiles, PVC containers, children's toys, etc.

[0188] In some preferred embodiments, the resin articles of the present invention can be products for use in the medical field, such as Luer connectors, indwelling needles, specimen containers, drip infusion sets, etc.

[0189] <<Example>>

[0190] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0191] <Evaluation Methods>

[0192] The composition ratio of each structural unit of the rigid vinyl chloride copolymer, the number-average molecular weight and molecular weight distribution (PDI) of the copolymer, mechanical properties, processability, self-plasticizing properties, migration resistance, biocompatibility, and transparency were evaluated using the following methods.

[0193] (Copolymer composition ratio)

[0194] The copolymer composition ratio was determined using a Bruker AV400 nuclear magnetic resonance spectrometer (THF-d8 as solvent).

[0195] (N-average molecular weight and molecular weight distribution (PDI) of copolymers)

[0196] The number-average molecular weight and molecular weight distribution of the copolymers were determined using a Waters-1515 gel permeation chromatography system with THF as the eluent and polystyrene as the standard.

[0197] (Mechanical properties)

[0198] 100 parts of a vinyl chloride copolymer (or polyvinyl chloride in the reference example) and 2 parts of a methyl tin mercaptan heat stabilizer were mixed together using a two-roll mill. The mixture was then hot-pressed at 175°C for 5 minutes and cold-pressed for 5 minutes to obtain sample pieces (15cm × 15cm × 2mm). The obtained sample pieces were cut into dumbbell-shaped strips, and their tensile strength and elongation at break were determined according to GB / T 1040-2006.

[0199] (Processability)

[0200] Processability was evaluated using a torque rheometer. Specifically, 100 parts of a vinyl chloride copolymer (or polyvinyl chloride in the reference example) were mixed uniformly with 2 parts of methyltin mercaptan heat stabilizer, and then tested in a Brabender internal mixer at 175°C for 10 minutes. Processability was evaluated using equilibrium torque.

[0201] The reduction in equilibrium torque of the vinyl chloride copolymers obtained in each embodiment and comparative example relative to the equilibrium torque of the homopolymer polyvinyl chloride obtained in the reference example was calculated using the following formula (1).

[0202] Formula (1): Reduction degree = (balance torque of homopolymer polyvinyl chloride - balance torque of vinyl chloride copolymer) / (balance torque of homopolymer polyvinyl chloride) × 100%.

[0203] In this invention, a reduction of 0-5% is defined as poor, a reduction of more than 5% and less than 10% is defined as good, a reduction of more than 10% and less than 20% is defined as excellent, and a reduction of more than 20% is defined as optimal.

[0204] (Self-plasticizing properties)

[0205] Self-plasticity was evaluated using the glass transition temperature (Tg). Samples were prepared using the same method as described in the mechanical property evaluation. The resulting samples were cut into strips 5 mm wide and 75 mm long, and the glass transition temperature was tested using a DMTA2980. The test mode was tensile, the test frequency was 1 Hz, and the temperature range was -60℃ to 150℃.

[0206] (Migration resistance)

[0207] In this invention, the evaluation of migration resistance is whether there are substances in the vinyl chloride copolymer that are prone to migration due to the introduction of plasticizing segments into the molecular chain.

[0208] Samples were prepared using the same method as described in the evaluation of the mechanical properties above. Each sample was then cut into two parallel sets of five pieces each, weighed, and the weight recorded. The two sets of cut samples were then immersed in ethanol and water, respectively, at room temperature for 48 hours. Finally, they were removed and dried in a 50°C oven for 24 hours before being weighed. The percentage difference in mass between the sample before and after immersion (in ethanol or water) was calculated relative to the mass of the sample before immersion, and the average of this percentage was defined as the migration rate. It is important to note that the migration rate should be ≤0.1%.

[0209] (Biological)

[0210] Samples were prepared using the same method as described in the evaluation of the mechanical properties above. Hemolytic and cytotoxicity tests were performed on the samples according to GB / T16886.5 and GB / T16886.12.

[0211] It should be noted that the hemolysis rate value in GB / T 16886.5 and GB / T16886.12 requires R < 5%. In this invention, R ≥ 5% is defined as poor, 2.5% ≤ R < 5% is defined as good, 0.5% ≤ R < 2.5% is defined as excellent, and R < 0.5% is defined as optimal.

[0212] (Transparency)

[0213] Samples were prepared using the same method as described in the evaluation of the mechanical properties above. Light transmittance in the wavelength range of 500–800 nm was measured using a UV-Vis spectrophotometer. In this invention, light transmittance below 75% is defined as poor, light transmittance above 75% and below 78% is defined as good, light transmittance above 78% and below 82% is defined as excellent, and light transmittance above 82% is defined as optimal.

[0214] <Example 1>

[0215] In a 500ml stainless steel microreactor, 200g of deionized water, 20.8g of a 2% PVA aqueous solution, 0.149g of azobisisobutyronitrile (AIBN), and 5.4g of 2-ethylhexanoate monomer (V2EH) were added. Nitrogen gas was then introduced into the reactor for 5 minutes to replace the air. Then, 102.6g of vinyl chloride (VC) monomer was introduced into the reactor. After pre-stirring for 30 minutes, the temperature was raised to 50℃ to begin polymerization. It should be noted that the monomer feed mass ratio of VC:V2EH was 95:5, and the polymerization reaction time was 8 hours. After the polymerization reaction was completed, the unreacted VC monomer was recovered, and the polymerization product was washed alternately with a large amount of deionized water and ethanol to obtain 97.5g of white solid granules of vinyl chloride copolymer. Its composition was: relative to the total mass of the vinyl chloride copolymer (100% by mass), the content of structural unit (a) was 95.2% by mass, and the content of structural unit (b) was 4.8% by mass.

[0216] <Example 2>

[0217] The polymerization and post-treatment were carried out using the same steps as in Example 1. It should be noted that the monomer feed mass ratio VC:V2EH = 90:10. The composition of the resulting resin is as follows: relative to the total mass of the vinyl chloride copolymer, the content of structural unit (a) is 90.8% by mass and the content of structural unit (b) is 9.2% by mass.

[0218] <Example 3>

[0219] The polymerization and post-treatment were carried out using the same steps as in Example 1. It should be noted that the monomer feed mass ratio VC:V2EH = 85:15. The composition of the resulting resin is as follows: relative to the total mass of the vinyl chloride copolymer, the content of structural unit (a) is 84.2% by mass and the content of structural unit (b) is 15.8% by mass.

[0220] <Example 4>

[0221] The polymerization and post-treatment were carried out using the same steps as in Example 1. It should be noted that the monomer feed mass ratio VC:V2EH = 98:2. The composition of the resulting resin is as follows: relative to the total mass of the vinyl chloride copolymer, the content of structural unit (a) is 97.8% by mass and the content of structural unit (b) is 2.2% by mass.

[0222] <Example 5>

[0223] In a 500ml stainless steel microreactor, 200g of deionized water, 20.8g of a 2% PVA aqueous solution, 0.149g of azobisisobutyronitrile (AIBN), 5.4g of vinyl 2-ethylhexanoate monomer (V2EH), and 5.4g of isooctyl acrylate (EHA) were added. Nitrogen gas was then introduced into the reactor for 5 minutes to replace the air. Next, 97.2g of VC monomer was introduced into the reactor. After pre-stirring for 30 minutes, the temperature was raised to 50℃ to begin polymerization. It should be noted that the monomer mass ratio of VC:V2EH:EHA is 90:5:5, and the polymerization reaction time is 8 hours. After the polymerization reaction was completed, the unreacted VC monomer was recovered, and the polymerization product was washed alternately with a large amount of deionized water and ethanol to obtain 98.6 g of white solid particles of vinyl chloride copolymer. The composition of the obtained resin was as follows: relative to the total mass of the vinyl chloride copolymer (100% by mass), the content of structural unit (a) was 89.6% by mass, the content of structural unit (b) was 4.4% by mass, and the content of structural unit (c) was 6.0% by mass.

[0224] <Example 6>

[0225] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that the mass ratio of monomers fed was VC:V2EH:EHA = 90:0.2:9.8. The composition of the resulting resin was as follows: relative to the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 89.5% by mass, the content of structural unit (b) was 0.2% by mass, and the content of structural unit (c) was 10.3% by mass.

[0226] <Example 7>

[0227] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that the mass ratio of monomers fed was VC:V2EH:EHA = 90:9.5:0.5. The resulting resin had the following composition: relative to the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 89.5% by mass, the content of structural unit (b) was 9.9% by mass, and the content of structural unit (c) was 0.6% by mass.

[0228] <Example 8>

[0229] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that the mass ratio of monomers fed was VC:V2EH:EHA = 85:5:10. The composition of the resulting resin was as follows: relative to the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 82.5% by mass, the content of structural unit (b) was 4.7% by mass, and the content of structural unit (c) was 12.8% by mass.

[0230] <Example 9>

[0231] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that the monomer feed mass ratio VC:V2EH:EHA = 85:10:5. The composition of the resulting resin is as follows: relative to the total mass of the vinyl chloride copolymer, the content of structural unit (a) is 83.8% by mass, the content of structural unit (b) is 10.7% by mass, and the content of structural unit (c) is 5.5% by mass.

[0232] <Example 10>

[0233] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that the mass ratio of monomers fed was VC:V2EH:EHA = 80:10:10. The composition of the resulting resin was as follows: relative to the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 80.8% by mass, the content of structural unit (b) was 9.7% by mass, and the content of structural unit (c) was 9.5% by mass.

[0234] <Example 11>

[0235] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that the mass ratio of monomers fed was VC:V2EH:EHA = 80:2:18. The composition of the resulting resin was as follows: relative to the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 80.3% by mass, the content of structural unit (b) was 2.3% by mass, and the content of structural unit (c) was 17.4% by mass.

[0236] <Example 12>

[0237] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that the monomer feed mass ratio VC:V2EH:EHA = 80:18:2. The composition of the resulting resin is as follows: relative to the total mass of the vinyl chloride copolymer, the content of structural unit (a) is 80.2% by mass, the content of structural unit (b) is 17.0% by mass, and the content of structural unit (c) is 2.8% by mass.

[0238] <Example 13>

[0239] The polymerization and post-treatment were carried out using the same steps as in Example 8. It should be noted that the monomer EHA was replaced with methyl methacrylate (MMA). The resulting resin had the following composition: relative to 100% of the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 81.3% by mass, the content of structural unit (b) was 4.8% by mass, and the content of structural unit (c) was 13.9% by mass.

[0240] <Example 14>

[0241] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that V2EH was replaced with the monomer shown in formula (1-5). The resulting resin had the following composition: relative to 100% of the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 89.8% by mass, the content of structural unit (b) was 4.6% by mass, and the content of structural unit (c) was 5.6% by mass.

[0242] <Example 15>

[0243] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that V2EH was replaced with vinyl pentanoate. The resulting resin had the following composition: relative to 100% of the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 89.6% by mass, the content of structural unit (b) was 4.8% by mass, and the content of structural unit (c) was 5.6% by mass.

[0244] <Example 16>

[0245] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that V2EH was replaced with 2-methylheptaethyl vinyl ester. The resulting resin had the following composition: relative to 100% of the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 89.3% by mass, the content of structural unit (b) was 5% by mass, and the content of structural unit (c) was 5.7% by mass.

[0246] <Example 17>

[0247] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that V2EH was replaced with 2-methylpropionic acid vinyl ester. The resulting resin had the following composition: relative to 100% of the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 90.3% by mass, the content of structural unit (b) was 4.5% by mass, and the content of structural unit (c) was 5.2% by mass.

[0248] <Comparative Example 1>

[0249] In a 500ml stainless steel microreactor, 200g of deionized water, 20.8g of a 2% PVA aqueous solution, 0.149g of azobisisobutyronitrile (AIBN) initiator, and 16.2g of EHA were added. Nitrogen gas was then introduced into the reactor for 5 minutes to replace the air. Next, 91.8g of VC monomer was introduced into the reactor. After pre-stirring for 30 minutes, the temperature was raised to 50℃ to begin polymerization. It should be noted that the monomer feed ratio of VC:EHA was 85:15, and the polymerization reaction time was 8 hours. After the polymerization reaction was completed, the unreacted VC monomer was recovered, and the polymerization product was washed alternately with a large amount of deionized water and ethanol to obtain 89.36g of white solid granules of vinyl chloride copolymer. The composition of the obtained resin was: relative to the total mass of the vinyl chloride copolymer (100% by mass), the content of structural unit (a) was 82.5% by mass, and the content of structural unit (c) was 17.5% by mass.

[0250] <Comparative Example 2>

[0251] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that the monomer feed mass ratio VC:V2EH:EHA = 70:10:20. The resulting resin composition is as follows: relative to 100% of the total mass of the vinyl chloride copolymer, the content of structural unit (a) is 68.7% by mass, the content of structural unit (b) is 9.8% by mass, and the content of structural unit (c) is 21.5% by mass.

[0252] <Comparative Example 3>

[0253] The polymerization and post-treatment were carried out using the same steps as in Example 5. It should be noted that the mass ratio of monomers fed was VC:V2EH:EHA = 99.5:0.25:0.25. The resulting resin had the following composition: relative to 100% of the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 99.5% by mass, the content of structural unit (b) was 0.2% by mass, and the content of structural unit (c) was 0.3% by mass.

[0254] <Comparative Example 4>

[0255] The polymerization and post-treatment were performed using the same steps as in Example 5, except that V2EH was replaced with vinyl acetate (VAc). The resulting resin had the following composition: relative to 100% of the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 82.6% by mass, the content of structural unit (b) was 4.6% by mass, and the content of structural unit (c) was 12.8% by mass.

[0256] <Comparative Example 5>

[0257] The polymerization and post-treatment were performed using the same steps as in Example 5, except that V2EH was replaced with vinyl octanoate. The resulting resin had the following composition: relative to 100% of the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 89.7% by mass, the content of structural unit (b) was 5.1% by mass, and the content of structural unit (c) was 5.2% by mass.

[0258] <Comparative Example 6>

[0259] The polymerization and post-treatment were performed using the same steps as in Example 1, except that the VC:V2EH ratio was changed from 95:5 to 78:22. The resulting resin had the following composition: relative to 100% mass of the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 78.5% by mass, and the content of structural unit (b) was 21.5% by mass.

[0260] <Comparative Example 7>

[0261] The polymerization and post-treatment were performed using the same steps as in Example 1, except that the VC:V2EH ratio was changed from 95:5 to 99.5:0.5. The resulting resin had the following composition: relative to 100% of the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 99.3% by mass, and the content of structural unit (b) was 0.7% by mass.

[0262] <Comparative Example 8>

[0263] The polymerization and post-treatment were performed using the same steps as in Example 1, except that V2EH was replaced with vinyl acetate (VAc). The resulting resin had the following composition: relative to 100% of the total mass of the vinyl chloride copolymer, the content of structural unit (a) was 95.5% by mass, and the content of structural unit (b) was 4.5% by mass.

[0264] <Reference Example>

[0265] The polymerization and post-processing were performed using the same steps as in Example 1, except that only VC monomer was used as the polymerization monomer. Homopolymer polyvinyl chloride was obtained in the reference example.

[0266]

[0267]

[0268]

[0269] Note: In Table 3, in Comparative Examples 4 and 8, the amounts marked with "(b)" are the amounts of VAc-based structural units, and in Comparative Example 5, the amounts marked with "(b)" are the amounts of vinyl octanoate-based structural units. In Comparative Example 6, when the amount of V2EH was 21.5, the processing viscosity of the copolymer resin was too low, resulting in severe roller sticking and making it unsuitable for practical applications.

[0270] It should be noted that although the technical solution of the present invention has been described with specific examples, those skilled in the art will understand that the present invention should not be limited thereto.

[0271] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or technical improvements to the embodiments in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.

Claims

1. A rigid vinyl chloride-based copolymer, characterized in that, include: Structural units based on vinyl chloride (a), structural units based on monomers shown in equation (1) (b), and structural units based on monomers shown in equation (2) (c), (1) In formula (1), R1 is selected from hydrogen and alkyl groups having 1 to 6 carbon atoms; R2 is selected from alkyl groups having 1 to 5 carbon atoms; each R3 is independently selected from hydrogen and alkyl groups having 1 to 22 carbon atoms, but not simultaneously hydrogen. (2) In formula (2), R4 is selected from hydrogen and methyl, and R5 is selected from alkyl with 1 to 18 carbon atoms, hydroxyalkyl with 1 to 18 carbon atoms, alkoxyalkyl with 1 to 18 carbon atoms, aminoalkyl with 1 to 18 carbon atoms, and cycloalkyl with 3 to 18 heteroatoms. The total content of structural units (b) and (c) is 1-20% by mass relative to 100% of the total mass of the rigid vinyl chloride copolymer. In the rigid vinyl chloride copolymer, the mass ratio of structural unit (b) to structural unit (c) is 1 / 20 to 10 / 1.

2. The rigid vinyl chloride copolymer according to claim 1, characterized in that, In formula (1), R1 is selected from hydrogen and methyl; R2 is selected from alkyl groups having 1 to 4 carbon atoms; each R3 is independently selected from hydrogen and alkyl groups having 1 to 18 carbon atoms, but not simultaneously from hydrogen.

3. The rigid vinyl chloride copolymer according to claim 1 or 2, characterized in that, In formula (2), R5 is selected from alkyl groups having 1 to 10 carbon atoms, hydroxyalkyl groups having 1 to 10 carbon atoms, alkoxyalkyl groups having 1 to 10 carbon atoms, aminoalkyl groups having 1 to 10 carbon atoms, and cycloalkyl groups having 3 to 10 heteroatoms.

4. The rigid vinyl chloride copolymer according to claim 1 or 2, characterized in that, The content of structural unit (b) is 0.5 to 19% by mass relative to 100% of the total mass of the rigid vinyl chloride copolymer.

5. The rigid vinyl chloride copolymer according to claim 1 or 2, characterized in that, The content of structural unit (c) is 1 to 19.5% by mass relative to 100% of the total mass of the rigid vinyl chloride copolymer.

6. The rigid vinyl chloride copolymer according to claim 1 or 2, characterized in that, In the rigid vinyl chloride copolymer, the mass ratio of structural unit (b) to structural unit (c) is 1 / 15 to 2 / 1.

7. The rigid vinyl chloride copolymer according to claim 1 or 2, characterized in that, The rigid vinyl chloride copolymer has a tensile elongation at break of less than 140%; the number average molecular weight of the rigid vinyl chloride copolymer is 40,000 to 250,000.

8. A method for preparing a rigid vinyl chloride copolymer according to any one of claims 1 to 7, characterized in that, It includes: performing a copolymerization reaction of raw materials including vinyl chloride, the monomer shown in formula (1) and the monomer shown in formula (2).

9. A vinyl chloride-based resin composition, characterized in that, It includes rigid vinyl chloride copolymers according to any one of claims 1 to 7.

10. A resin product, characterized in that, It is made from the vinyl chloride-based resin composition according to claim 9.

Citation Information

Patent Citations

  • Rigid polyvinyl chloride copolymer, method for producing rigid polyvinyl chloride copolymer, composition comprising rigid polyvinyl chloride copolymer, and resin product produced from composition

    CN112574349A

  • Novel chlorine-containing multipolymers and process for the preparation thereof

    GB1128580A

  • Coating composition

    GB1146419A

  • Vinyl Tile Composition.

    GB1155340A

  • Foamed plastics from vinyl polymer dispersions and process for their manufacture

    US3639297A